EFEKTIVITAS PENDEKATAN OPEN ENDED DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Dewi, Putri Sukma (Universitas Suryakancana, 2018)
ABSTRACT Students' mathematical problem solving ability is one of mathematic thinking skills that students must have. Application of open-ended approach is expected to improve that ability. The research design used is a quasi-experimental design, it’s post-test only with population of all students class VII SMP Negeri 1 Bandar Sribhawono academic year 2010/2011. Through Purposive Random Sampling technique obtained class VII.4 and VII.5 as sample research. Based on the data analysis, it was found that: (1) more than 50% of students in the experimental class were thoroughly studied, and (2) the average mathematical problem solving ability in the learning with the open-ended approach was higher than the conventional learning. So it is concluded that the application of an effective open-ended approach is viewed from students' mathematical problem solving ability.Keywords: Rectangle, Open-Ended Approach and Troubleshooting